QRIS Payment Innovation: Strategic Steps to Increase MSMEs in Rejosari Village - Budi Cahyono; Farhah Ani Karimatul Akhlaq; Abiel Marfuzan; Muhammad Rabbith Fu'adi; Nur Khumairoh Nafisatuz Zahroh; Nanda Ayu Listyaningrum; Titisari Azizah Wijayanti; Akhriyadi Sofian (Universitas Palangka Raya, 2024)
Bank Indonesia and the Indonesian Payment System Association (ASPI) launched QRIS on August 17, 2019, with its effective implementation starting on January 1, 2020. QRIS is a standard designed to facilitate payments through QR codes in Indonesia. This study examines the implementation of the QRIS (Quick Response Code Indonesian Standard) payment system as a strategic innovation to drive the growth of Micro, Small, and Medium Enterprises (MSMEs) in Rejosari Village. Using a descriptive qualitative research method, this study explores the impact of QRIS adoption on transaction efficiency, financial inclusion, and the competitiveness of local MSMEs. The research findings show that the implementation of QRIS significantly increased the volume of non-cash transactions, expanded access to digital financial services, and facilitated the integration of MSMEs into the digital economy ecosystem. Key challenges identified include the digital literacy gap among MSME players and the limitations of technological infrastructure in rural areas. This study concludes that QRIS payment innovation is a crucial catalyst in the digital transformation of MSMEs in Rejosari Village, with recommendations to enhance digital guidance programs and develop supporting infrastructure to optimize local economic growth potential.